Formation and Breakdown of the Solid-electrolyte Interphase in a Bis(fluorosulfonyl)amide-based Ionic Liquid in the Presence of Lithium Ion - Sho OKAZAKI; Nobuyuki SERIZAWA; Yasushi KATAYAMA (Electrochemistry, 2024)
The formation and breakdown of the solid electrolyte interphase (SEI) on a Pt electrode were investigated in 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl)amide (BMPFSA) containing a high concentration of LiFSA using a ferrocene/ferrocenium couple as a redox probe. The formation of the SEI was confirmed at the potential more negative than −1.1 V vs. Ag|Ag(I). However, the SEI was found to disappear at the open circuit potential. The SEI was suggested to form by the dissolution and/or dispersion of the decomposition products in the electrolyte.